Vulnerability Analysis and Mitigation of Web Applications Using Static Code Analysis and SSDLC Approach - Evan Samuel Reinheart Mamesah; Jimmy Herawan Moedjahedy (SAGA: Journal of Technology and Information System, 2026)
In today's age of technology, web applications have become essential parts of the environment. Due to easy accessibility of the internet, the user can engage in actions without considering the possible impact, leading individuals and organizations to commit such actions freely. As a result, there has been an upsurge in cyber-attacks against web applications that are prone to attacks. Mitigation is achieved using static code analysis with SonarQube in order to detect vulnerabilities within the web application code. In this case, the aim is to contribute to developers through the recommendation on how to develop their web applications while considering security aspects. SSDLC is utilized to manage the web application used during the simulation of the cyber-attacks and mitigation of the impacts thereof. Results are reported as comparisons made before and after mitigation. Before implementation of mitigation measures, the web application was vulnerable to all simulated cyber-attacks. After implementation of mitigation measures, it became clear from analyses that the attack had no way of exploiting the secured vulnerabilities.